Are Ancient Durum Wheats Less Toxic to Celiac Patients? A Study of α-Gliadin from Graziella Ra and Kamut - M. Stella Colomba; Armando Gregorini (The Scientific World Journal)
In the present paper, the controversial hypothesis suggesting ancient grains might show lower immunogenic properties and therefore the possibility to introduce them in the diet of wheat-sensitive people, including celiac patients, was investigated. The immunogenic potential of the ancient durum wheats Graziella Ra and Kamut was studied by comparison to the durum accessions Cappelli, Flaminio, Grazia and Svevo. Experiments were carried out with two monoclonal antibodies (mAbs) raised against α-gliadin peptides p31–49 and p56–75 (the latter containing the overlapping DQ2-Glia-α1 and DQ2-Glia-α2 epitopes), toxic for celiac patients. For all accessions, a few α-gliadin alleles were also cloned, sequenced and translated into aminoacid sequences. Several aminoacid substitutions or deletions were detected in p31–49, DQ2-Glia-α1 and DQ2-Glia-α2 epitopes, nevertheless, ELISA constantly showed antibody-antigen positive reactions which led us to suggest that mAbs binding was not apparently affected by polymorphisms. Moreover, a few substitutions were also observed in DQ2-Glia-α3 and DQ8-Glia-α1 epitopes. Although some DQ2-Glia-α1 and DQ2-Glia-α2 variants evidenced herein were previously reported to have a diminished or abolished T cell stimulatory capacity, present results cannot confirm that ancient durum wheats would be less CD-toxic. In conclusion, we strongly advice celiac patients from consuming ancient wheats including Graziella Ra or Kamut.